Laboratory animal allergy: anaphylaxis from a needle injury. - Watt, A D (1996)
A 32 year old male research physician accidentally received a minor wound from a needle which had been previously used on rabbit tissue. Within 15 minutes serious anaphylactic reactions started and he was taken to hospital where his condition stabilised within five hours. Serum immunoglobulin E antibodies to rabbit epithelium were high (16.2 U/ml), although other antibody titres were low. Allergy tests were not carried out before employment, so this alarming scenario could not have been predicted. People with confirmed laboratory animal allergy should be warned of the dangers of continued unprotected exposure and avoidance of the allergen should be encouraged by good laboratory practice and respiratory protective equipment.